Total kandungan antioksidan ekstrak etanol buah beringin (Ficus benjamina Linn.) - Anderson Arnold Aloanis; Marlina Karundeng (Jurnal Kimia Fullerene, 2019)
Nowadays the need for antioxidants is increasing. Advances in technology and sciences encourage an increase in the number of free radicals and oxidizing compounds. This study aims to measure the total antioxidant content of the ethanolic extract of beringin (Ficus benjamina Linn.) fruit. Measurement of total antioxidant capacity begins with extraction by maceration. The freshly picked banyan fruit is macerated using 95% ethanol for 3 × 24 hours. Maceration is carried out at room temperature and kept away from sunlight. The macerated filtrate is then evaporated to get a thick ethanol extract. The ethanol extract was then measured for its antioxidant ability using phosphomolybdenum assay. Measurement using UV-Vis spectrophotometer. The measurement results showed the antioxidant activity of ethanol extract is 43.73 mg / gram AAE.